Solving the Course - Classroom Assignment Problem for a University - Thongsanit, Kanjana (Science, Engineering and Health Studies, 2014)
A large number of courses and the different classroom capacities with difference in study periods make the assignment between classrooms and courses complicated. The scheduler always takes long time to solve the problem. The purpose of the study is to develop mathematical model and design methods to solve the problem. The assignment problem uses the information from the Faculty of Engineering and Industrial Technology at Silpakorn University in the first semester, 2012. Excel’s Premium Solver is applied in this study. It was found that Excel’s Premium Solver can solve this classroom allocation problem with the process time in seconds. The total cost was reduced 27,920 baht / semester.